2007
DOI: 10.1016/j.carbon.2006.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Br treated graphite nanoplatelets for improved electrical conductivity of polymer composites

Abstract: The graphite nanoplatelets (GNP) were treated by vapor-phase bromination. The increase in weight and atomic concentration of Br indicated the bromine uptake. The intercalation of Br between graphene layers of GNP was confirmed by the X-ray diffraction result, showing an increase in the interlayer spacing from 3.342 Å to 3.361 Å. Two types of bonds between C and Br were introduced simultaneously, ionic and covalent bonds, both of them increased with bromination duration. The fraction of ionic bond reached the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 11 publications
7
101
1
Order By: Relevance
“…Using simulation in physics allows the number of experiments to be reduced and thus time and cost for development at laboratory and industry scale by linking theory and experimentation [10][11][12][13][14][15][16]. Functionalisation of nanoparticles, when they are dispersed in an epoxy resin, could have two aims: improving the dispersion quality by decreasing the interaction between nanoparticles [17][18][19], and improving the mechanical properties of the composite by improving the interfacial bonding between matrix, nanoparticles and micro-reinforcement [20][21][22][23]. When nanoparticles are dispersed in an epoxy resin, they have a tendency to re-agglomerate and create only weak bonds with the epoxy molecules by Van der Waals interaction.…”
Section: Fabrication Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using simulation in physics allows the number of experiments to be reduced and thus time and cost for development at laboratory and industry scale by linking theory and experimentation [10][11][12][13][14][15][16]. Functionalisation of nanoparticles, when they are dispersed in an epoxy resin, could have two aims: improving the dispersion quality by decreasing the interaction between nanoparticles [17][18][19], and improving the mechanical properties of the composite by improving the interfacial bonding between matrix, nanoparticles and micro-reinforcement [20][21][22][23]. When nanoparticles are dispersed in an epoxy resin, they have a tendency to re-agglomerate and create only weak bonds with the epoxy molecules by Van der Waals interaction.…”
Section: Fabrication Challengesmentioning
confidence: 99%
“…Despite the inert surface of graphene, Sharma et al [47] showed that some chemical groups can be reactive to it. The effect of bromine functionalised GNP on the mechanical and electrical properties of composites was also studied [22]. The presence of bromine caused the formation of ionic and covalent bonds with the matrix, improving the flexibility of the composites, and the electrical conductivity.…”
Section: Functionalisationmentioning
confidence: 99%
“…It has been used recently to build various nanocomposites which exhibit enhanced electronic and adsorption properties. [5][6][7][8][9][10] The graphene layers of GO are stacked together with an interlayer distance varying from 6-12 Å depending on the level of hydration. [11] Oxidation of graphite causes introduction of epoxy and hydroxyl groups to the graphene layers, as well as carboxylic groups mainly located on the edges of the layers.…”
Section: Introductionmentioning
confidence: 99%
“…(Additional evidence for the decrease in nitrile group concentration and their partial polymerization to form a conjugated imine system was received by FTIR analysis [6].) Doping of PAN with Br was monitored by recording the weight increase and by X-ray photoelectron spectroscopy (XPS) analysis of the proportion of ionic/covalent Br as a function of exposure time, as done in our previous study of Br treated graphite nanoplatelets [10]. However, because at this stage we were unable to identify consistent trends, only the results of 8 and 10% Br weight increase, respectively, are reported.…”
Section: Resultsmentioning
confidence: 99%